An investigation into the design of a jacket or template oil producing platform to be situated on the Agulhas bank - Neser, G. E.(Grant Edward) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1986.